Carbon Emission Characteristics and Reduction Pathways of Urban Household in China - Li, Zhi; Liu, Yuze; Zhang, Zuo (Frontiers in Environmental Science, 2022)
With China’s rapid urbanization and rising living standards, the household sector has become the second largest contributor to urban carbon emissions and important pathway to achieve China’s carbon reduction targets. Based on data of Chinese Residential Energy Consumption Survey in 2014, this paper establishes standard households in 54 cities to identify the carbon emission characteristics and explores the emission reduction paths of urban households. We present evidence that rich households tend to increase their use of clean energy, low-income households will not completely abandon inferior energy because of their usage habits and costs and they always live in suburban areas and urban villages. Cities with high household carbon emissions are almost located in north of Huai River/Qinling Mountains line, while cities with low carbon emissions are mostly located around the line and which are mainly on the south side. Monocentric urban development patterns and frigid climates are easy to increase higher household carbon emissions. In this regard, policy makers should help low-income households to escape from inferior energy dependence, encourage the use of new energy vehicles and green housing technologies, introduce a two-part pricing system for central heating services and maintain relative balance of residential and public resources in urban planning.